Patient Experience and Views on Antiretroviral Treatment—Findings from the Positive Perspectives Survey. (4th October 2017) - Young, Benjamin; Spire, Bruno; Morcillo, Diego Garcia; Muchenje, Marvelous; Parkinson, Kneeshe; Krehl, Moritz; Marcotullio, Simone; Allan, Brent; Punekar, Yogesh; Namiba, Angelina; deRuiter, Annemiek; Barthel, Sophie; et al.
Abstract: Background: While advances in treatment have dramatically improved the life-expectancy of people living with HIV (PLHIV), a number of unmet needs remain. We conducted an international survey of PLHIV to explore their level of satisfaction with current treatment and potential areas of improvement for ARVs. Methods: Qualitative in-depth interviews were performed with PLHIV to identify key hypotheses. A steering group developed the survey questions which was fielded online from November 2016 to April 2017 in 9 countries across North America, Europe and Australia. A mixed sampling/recruitment approach was used to ensure a broad cross-section of PLHIV. Respondents were screened for eligibility prior to receiving access to the online survey Results: Overall 1085 PLHIV completed the survey with 40% of respondents from North America. The demographic breakdown was 25% women, 34% >50 years, 49% diagnosed >10 years ago, 76 % with co-morbidities. 40% had a college degree or higher, 33% were in full-time employment and 62% lived in a large city. Majority (98%) were currently taking ARVs with 53% taking a Single Tablet Regimen (STR). 87% of those diagnosed within last 2 years had started treatment within 6 months of diagnosis, compared with 40% of those diagnosed > 10 years ago. Of those on treatment, 87% were satisfied with their current ARV regimen. 33% had changed treatment in the last 12 months with the main reasons for switching being reducing severity or frequency of side effects (43%) and reducing the pill burden (31%). 73% of those on treatment were worried about the long-term effects of ARVs. Reducing these long-term effects (25%) and the potential availability of longer lasting treatments (21%) were identified as the 2 most important potential improvements to current regimens. 62% were open to changing to an ARV regimen with fewer drugs as long as their HIV remained suppressed. Demographics and results for the North American cohort were generally similar to the overall global results. Conclusion: In this international survey, the majority of PLHIV were satisfied with their current regimen, with reducing long-term adverse effects of ARVs and a longer lasting treatment identified as the most important potential improvements. Disclosures: B. Young, ViiV Healthcare: Consultant and Scientific Advisor, Consulting fee and Research support; Gilead: Consultant and Scientific Advisor, Consulting fee and Research support; Merck: Consultant, Scientific Advisor and Speaker's Bureau, Consulting fee and Research support; B. Spire, Gilead: Scientific Advisor, Consulting fee; MSD: Scientific Advisor, Consulting fee; D. Garcia Morcillo, ViiV Healthcare: Consultant, Consulting fee; K. Parkinson, ViiV Healthcare: Consultant, Consulting fee; M. Krehl, ViiV Healthcare: Consultant, Consulting fee; S. Marcotullio, Abbvie, Gilead sciences, Janssen-Cilag: Scientific Advisor, Consulting fee and Research grant; B. Allan, ViiV Healthcare: Consultant, Consulting fee; Y. Punekar, ViiV Healthcare: Employee and Shareholder, Salary; A. deRuiter, ViiV Healthcare: Employee and Shareholder, Salary; S. Barthel, GlaxoSmithKline: Employee and Shareholder, Salary; J. Koteff, ViiV Healthcare: Employee and Shareholder, Salary; C. Garris, ViiV Healthcare: Employee and Shareholder, Salary; C. Nguyen, ViiV Healthcare: Employee and Shareholder, Salary; A. Ustianowski, ViiV: Speaker's Bureau, Conference sponsorship; Gilead: Grant Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee, Grant recipient and Speaker honorarium; MSD: Scientific Advisor and Speaker's Bureau, Consulting fee and Speaker honorarium; Janssen: Scientific Advisor, Consulting fee; Abbvie: Grant Investigator, Grant recipient; P. Eitz Ferrer, ViiV Healthcare: Employee and Shareholder, Salary; A. Murungi, ViiV Healthcare: Employee, Salary